Organizational Communication Responses to Covid-19: Strategies and Practices - Dorien Kartikawangi; Rayini Dahesihsari (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2020)
In a crisis situation, employees are facing pressures and challenges because they have to deal with unexpected disruption in their routine working conditions with a high level of uncertainty. Organizational communication strategies and practices play important roles to give employees information, direction, and support. The research aims to explore how organizational communication strategies and practices responses to such a specific crisis: Pandemic Covid-19, using a situational crisis communication theoretical framework. The research applies a qualitative approach. Four organizations participated, involved two business organizations and two educational organizations, selected using a maximum variation sampling technique. Four people representing each organization were interviewed using the inductive method. Data were analyzed using thematic analysis. The findings show that organizational communication strategies and practices being used by all participantsâ€™ organizations are mostly related to the preparation stage and the response stage of crisis management. Early crisis management planning, forming crisis management teams, and preparing supporting communication systems, including providing health care facilities and communication protocols for infected employees are salient practices during the preparation stage. On the response stage, leader and horizontal communication intensively used with a variation of media and channels. Interestingly, informal communication was minimized while formal communication conducted intensively and transparently. Furthermore, sensitivity to employeesâ€™ needs and conditions as well as emphatic communication expressing positive emotion and support was perceived positive to help employees to understand the information well and to feel being understood and being appreciated.Â